Regulated Enzymes of Aromatic Amino Acid Synthesis: Control, Isozymic Nature, and Aggregation in Bacillus subtilis and Bacillus licheniformis - Nasser, Delill (1969)
Several regulated enzymes involved in aromatic amino acid synthesis were studied in Bacillus subtilis and B. licheniformis with reference to organization and control mechanisms. B. subtilis has been previously shown (23) to have a single 3-deoxy-d-arabinoheptulosonate 7-phosphate (DAHP) synthetase but to have two isozymic forms of both chorismate mutase and shikimate kinase. Extracts of B. licheniformis chromatographed on diethylaminoethyl (DEAE) cellulose indicated a single DAHP synthetase and two isozymic forms of chorismate mutase, but only a single shikimate kinase activity. The evidence for isozymes has been supported by the inability to find strains mutant in these activities, although strains mutant for the other activities were readily obtained. DAHP synthetase, one of the isozymes of chorismate mutase, and one of the isozymes of shikimate kinase were found in a single complex in B. subtilis. No such complex could be detected in B. licheniformis. DAHP synthetase and shikimate kinase from B. subtilis were feedback-inhibited by chorismate and prephenate. DAHP synthetase from B. licheniformis was also feedback-inhibited by these two intermediates, but shikimate kinase was inhibited only by chorismate. When the cells were grown in limiting tyrosine, the DAHP synthetase, chorismate mutase, and shikimate kinase activities of B. subtilis were derepressed in parallel, but only DAHP synthetase and chorismate mutase were derepressible in B. licheniformis. Implications of the differences as well as the similarities between the control and the pattern of enzyme aggregation in the two related species of bacilli were discussed.